PENGARUH KEGIATAN EKSTRAKURIKULER KEPRAMUKAAN TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK DI MTs MATHLA’UL HUDA PARUNG PANJANG BOGOR - Ahmad Dai Robi; Rahmawati Alwi (Institut Ummul Quro Al-Islami Bogor, 2024)
The background of this research is rooted in the importance of Extracurricular Scouting in helping to overcome student character problems. This extracurricular has a very significant role in educating and shaping the character of students. At present, we often encounter a lack of discipline in terms of student character, including disciplinary aspects related to time and performance, which affect the improvement of the character of students at MTs Mathla'ul Huda Parung Panjang Bogor. This study aims to see how Extracurricular Scouting can contribute to improving the character of students at MTs Mathla'ul Huda Parung Panjang Bogor. The purpose is to illustrate the influence of student character. This research is a type of descriptive research that uses a quantitative approach. The results showed the following: Extracurricular activities at MTs Mathla'ul Huda Parung Panjang Bogor were categorized as good. Descriptive statistics mean score of 113.42 standard deviations of 2.192 maximum or highest value of 117 minimum value of 208. The character of students at MTs Mathla'ul Huda Parung Panjang Bogor is categorized as good. Descriptive statistics: average score of 112.29, division standard 1.802, maximum score, highest score of 110, minimum score of 108. There is an influence of Scouting Extracurricular Activities on the Character Building of Students at MTs Mathla'ul Huda Parung Panjang Bogor with a significance of 0.000 < 0.05